Spatial Investigation on Noise Level at Sultan Idris Education University Campus, Malaysia. Issue 1 (May 2021) - Nayan, N; Hashim, M; Saleh, Y; Mahat, H; Luyan, Madeline Henry; Normelani, E; Juhadi, J; Khotimah, N; Sumunar, Dyah Respati Suryo
Abstract: This article aims to identify the level of spatial noise within the Universiti Pendidikan Sultan Idris Campus. This research is based on an exploratory study using quantitative methods and assisted by a geographic information system (GIS) software. The data used are primary data collected in the field based on sampling at 11 selected locations based on the main road intersection in the Sultan Abdul Jalil Shah Campus (KSAJS). Data collected with the help of the sound meter application in smartphones. Sampling time is from 8 am to 5 pm on weekdays. The analysis used is descriptive analysis and GIS regression technique, which is spatial interpolation to identify areas with the potential to experience high noise levels. The results show that some campus areas experience high noise levels in the morning and afternoon during the rush time going/back to/from work. Noise values ranging from 44.8 dBA to 66.4 dBA were obtained. The value indicates the maximum value exceeds the standard by the Department of Environment (DOE)(55 dBA). In conclusion, the noise level at KSAJS is acceptable due to the marginal use of vehicles on campus. This situation is due to a forbidden act to stop some students from using vehicles and maximizing the shuttle bus. This study's implications are important to be used as a guide to university administrators to maintain noise levels at the lowest level in creating a high-security environment, conducive learning environment, and a more peaceful working environment.